Solar proton events and stratospheric ozone depletion over northern Finland. (October 2018) - Denton, M.H.; Kivi, R.; Ulich, T.; Rodger, C.J.; Clilverd, M.A.; Horne, R.B.; Kavanagh, A.J.
Abstract: We examine the variation of stratospheric ozone over northern Finland using ozonesonde observations from 1845 stratospheric balloon flights launched between 1989 and 2015 from near Sodankylä. The annual variation of the ozone partial pressure is examined and seasonal variations are explored and quantified. Direct links between the measured ozone partial pressure and common solar-wind parameters are also examined. A superposed-epoch analysis of the observations based on 191 solar proton events (SPEs) reveals a clear drop in the ozone partial pressure that commences following SPE-arrival at Earth. This analysis shows a reduction in stratospheric ozone in the winter/early-spring months (when the polar vortex is active over northern Finland), in contrast to summer/early-autumn months where no decrease is detected. By subtracting the natural seasonal variations in ozone partial pressure the SPE-driven reduction in ozone between 16 km and 24 km altitude is quantified. Analysis indicates that the ozone partial pressure during winter/early-spring is reduced, with a minimum reached ∼8 days following the SPE arrival. On average, the ozone partial pressure is reduced by ∼10% between 16 and 24 km altitude and takes ∼40 days to return to its previous level. To the best of our knowledge, this is the first comprehensive statistical study, on a regional basis, that provides direct, and long-term in-situ evidence for ozone depletion by SPEs in the northern hemisphere. Highlights: No link between stratospheric ozone and geophysical indices (24 h lag). Stratospheric ozone falls ∼10% after solar proton events - below mean for ∼40 days. Ozone decrease only occurs during polar winter months, no effect in summer.